Anthropology of Our Times : An Edited Anthology in Public Anthropology - Bangstad, Sindre (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This anthology represents the culmination of a series of public discussions with some of the leading international anthropologists of today -organized by the editor, Sindre Bangstad-at the House of Literature in Oslo, Norway. Thus, it provides fresh and original insights into the lives and work of these leading scholars. It features conversations with Didier Fassin, Angelique Haugerud, Ruben Andersson, Claudio Lomnitz, David Price, Magnus Marsden, Richard Ashby Wilson, and Parvis Ghassem-Fachandi, in addition to an introduction by Sindre Bangstad and a preface by Thomas Hylland Eriksen.- Resumé vydavatel
Keywords: antropologie; antropologové; anthropology; anthropologists; elektronické knihy; rozhovory; electronic books; interviews